Fertility, Mortality and Environmental Policy - Ulla Lehmijoki; Tapio K. Palokangas (Institute of Labor Economics (IZA), 2016)
This article examines pollution and environmental mortality in an economy where fertility is endogenous and output is produced from labor and capital by two sectors, dirty and clean. An emission tax curbs dirty production, which decreases pollution-induced mortality but also shifts resources to the clean sector. If the dirty sector is more capital intensive, then this shift increases labor demand and wages. This, in turn, raises the opportunity cost of rearing a child, thereby decreasing fertility and the population size. Correspondingly, if the clean sector is more capital intensive, then the emission tax decreases the wage and increases fertility. Although the proportion of the dirty sector in production falls, the expansion of population boosts total pollution, aggravating mortality.
Keywords: J13; Q56; Q58; O41; 330; environmental mortality; pollution tax; population growth; two-sector models